Model driven software development: An overview - Saleem, M.Q. (Institute of Electrical and Electronics Engineers Inc., 2014)
The vision of the MDSD is an era of software engineering where modelling completely replaces programming i.e. The systems are entirely generated from high-level models, each one specifying a different view of the same system. The MDSD can be seen as the new generation of visual programming languages which provides methods and tools to streamline the process of software engineering. Productivity of the development process is significantly improved by the MDSD approach and it also increases the quality of the resulting software system. The MDSD is particularly suited for those software applications which require highly specialized technical knowledge due to the involvement of complex technologies and the large number of complex and unmanageable standards. In this paper, an overview of the MDSD is presented; the working styles and the main concepts are illustrated in detail. Â© 2014 IEEE.